2012
DOI: 10.4236/ns.2012.42015
|View full text |Cite
|
Sign up to set email alerts
|

Monoterpene hydrocarbons, major components of the dried leaves essential oils of five species of the genus Eucalyptus from Cote d’Ivoire

Abstract: The chemical composition of the essential oils obtained from the dried leaves of five species of the genus Eucalyptus (E. camaldulensis, E. deglupta, E. grandis, E. torelliana, E. urophylla) growing in Côte d'Ivoire, was analyzed by means of GC and GC/MS. The density and the refractive index were measured. The major components of all these oils are: α-pinene, β-pinene, α-phellandrene, limonene, γ-terpinene, p-cymene and β-caryophyllene. The particularity of these oils is their monoterpene hydrocarbons major co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
(27 reference statements)
2
5
0
Order By: Relevance
“…The eucalypt oil yielded by the RFD 2-6 clone was the highest among the E. urophylla clones. Regardless of clonal variations, the leaf essential oil yields of all the E. urophylla clones are related to those previously reported for the E. urophylla planted in the Congo [15], Lampang province, Thailand [18], Ethiopia [23], Brazil [24], and Côte d'Ivoire [27], ranging from 0.3 to 0.6%. Furthermore, the leaf essential oil yields of the E. urophylla and the E. urophylla × E. camaldulensis hybrid are higher than those reported by Li et al [29], with 0.04 and 0.16%, respectively (Table 2).…”
Section: Extraction Of Eucalypt Oilssupporting
confidence: 76%
See 1 more Smart Citation
“…The eucalypt oil yielded by the RFD 2-6 clone was the highest among the E. urophylla clones. Regardless of clonal variations, the leaf essential oil yields of all the E. urophylla clones are related to those previously reported for the E. urophylla planted in the Congo [15], Lampang province, Thailand [18], Ethiopia [23], Brazil [24], and Côte d'Ivoire [27], ranging from 0.3 to 0.6%. Furthermore, the leaf essential oil yields of the E. urophylla and the E. urophylla × E. camaldulensis hybrid are higher than those reported by Li et al [29], with 0.04 and 0.16%, respectively (Table 2).…”
Section: Extraction Of Eucalypt Oilssupporting
confidence: 76%
“…Additionally, our group [22] has reported that the dominant phenolic terpenoids (2.18-7.25%), thymol and carvacrol, cause the E. camaldulensis oils to have potent antioxidant properties (DPPH radical scavenging, and IC 50 values of 0.71-1.27 mg/mL), whereas the E. urophylla oil reported by Chahomchuen et al [18] contained a small amount of thymol (0.13%), and was shown to have weak DPPH radical scavenging activity (IC 50 19.95 mg/mL). However, only a few studies of E. urophylla and E. urophylla × E. camaldulensis leaf oils have been performed [15][16][17][18][23][24][25][26][27][28][29]. Variations in the antibacterial and antioxidant activity of eucalypt oils, on the other hand, are highly dependent on the type and abundance of bioactive compounds, which vary depending on the genus species, genetic backgrounds, planting sites, and seasonal variations [1,3,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…When compared with others research for the same species of eucalyptus, oil yield value in this study was quite high. The yield obtained for the same species E. urophylla reported by Coffi et al (2012) was 0.4%. As for the other species as Eucalyptus camadulensis, E. deglupta, E. grandis, and E. torelliana were 0.70%; 0.7%; 0.54%, and 0.20%, respectively (Coffi et al, 2012) and for E. pellita was 0.89% (Astiani, 2014).…”
Section: Oil Yieldsupporting
confidence: 57%
“…The main compounds in E. urophylla oil species derived from Congo were α -pinene (10.1%), 1,8-cineole (57.7%), and limonene (6.4%)(Cimanga et al, 2002). Other researches found that the main compound of E. urophylla from Brazil were α -pinene (13.3%), 1,8-cineole (44.7%), and α -terpinyl acetate (11.7%)(Coffi et al, 2012), and from Ethopia were α -pinene (15.6%), β -pinene (9.1%), 1,8-cineole (34.5%), and α -terpinyl acetate (11.6%)(Kambu et al, 1982).Singh et al (1988) also found that there were differences in the main compounds of E.…”
mentioning
confidence: 96%
“…Stamens, the creamy fruit is large and ovoid shape and with valves well below rim of the fruit. Ecalyptus has over 800 species and it is the second most widely planted multipurpose woody tree species in the world occurring under a wide range of environmental conditions [3,4]. The remarkable adaptability of Eucalypts coupled with their fast growth and superior wood properties has driven their rapid adoption for plantation forestry in more than 100 countries [4].…”
Section: Introductionmentioning
confidence: 99%